Peleraian Buah Sawit dari Tandan Menggunakan Kaedah Kimia - Ahmad, Desa; Jamaluddin, Hishamuddin; Gan, Lem Sing (Universiti Putra Malaysia Press, 1997)
A study was conducted on the effectiveness of a chemical substance, ethephon, on the 100 ening of oil palm fruit lets. Factors considered in the study were storage period, degree of ripeness, region and layer of spikelets within the oil palm bunch. Ethephon was poured into the stalk through a hole made using an electrical auger. The results obtained were analysed statistically using ANOVA and showed that the loosening of oil palm fruitlets was affected significantly by storage period, degree of ripeness and layer of spikelets within the bunch, but not by the region of spikelets.